Pengaruh Penyuluhan Dengan Media Leaflet Terhadap Pengetahuan Ibu Tentang Pencegahan Stunting Pada Balita Usia 12-36 Bulan Di Wilayah Kerja Puskesmas Ambalawi Kabupaten Bima - Putriani, Nining; Aprianti, Nurannisa Fitria; Yusuf, Nurlathifah N (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Stunting is an indicator of chronic malnutrition due to insufficient food intake for a long time, poor food quality, increased morbidity and an increase in height that does not match the age. Stunting data at the Ambalawi Health Center in 2022 in February were 260 and in August there were 8,431 (22.5%) of 1295 toddlers. To determine the effect of leaflet media counseling on mothers' knowledge about stunting prevention in toddlers aged 12-36 months in the Working Area of the Ambalawi Health Center. This research is a quantitative method with a Two Group Pre-Post Test design. The population is mothers who have toddlers aged 12-36 months in the Working Area of the Ambalawi Health Center in October-November as many as 100 people. Sampling used purposive sampling so that a total sample of 50 people was obtained. The instrument uses a questionnaire with the Wilcoxon chi test. Knowledge of mothers who have toddlers aged 12-36 months before counseling is carried out using leaflet media about stunting prevention in toddlers in the Working Area of the Ambalawi Health Center, Bima Regency, most of them are in the less category as many as 24 people (48.0%) and after being given some counseling 35 people (70.0%) were in the good category and there was an effect of counseling using leaflet media on mothers' knowledge about stunting prevention in toddlers aged 12-36 months in the Working Area of the Ambalawi Health Center (p value = 0.000 <0.05). Providing counseling using leaflet media can increase mother's knowledge about stunting prevention. The more actively the mother participates in counselling activities, the better her knowledge will be.